(untitled) (Czech Journal of International Relations, 1966)
The meaning of politics is what the current Prime Minister of Great Britain called his collection of speeches and statements from 1956 to 1963. It describes his position as a spokesman for the opposition Labor Party and, since February 1963, its leader, on a wide range of economic, domestic, foreign and military issues. The study of the collection enables not only a critical evaluation of the basic positions of the Labor Party and their program, but especially its confrontation with practical politics, as they have been carried out since October 1964, when they came to power. Wilson, a tired economist in England and until 1961 spoke to the opposition Labor Party on financial issues (shadow chancellor), economic issues (chapters II and III) is given primary attention. His speeches from this period are critical by the conservative government’s "stop-go" policy and its inability to achieve dynamic and sustained growth of the British economy, to consolidate the currency position and to keep the inflationary process in bearable proportions. At the forefront of economic policy, the Labor Party would like to draw up a five- to five-year plan for the steady and even development of the economy, and assigns an important place in it to measures to support exports. It demands the implementation of structural changes, the modernization of production and the harmonization of income with the growth of labor productivity.